The Efforts To Improve Student's Interest In Learning Mathematics By Using The Ctl (Contextual Teaching And Learning) Learning Model In Muhammadiyah 8 Middle Students In Medan T.P 2018/2019 - Enda Aprilia Shanti; Zainal Aziz (Indonesian Journal of Education and Mathematical Science, 2021)
In this study, the problem is that the students' interest in learning Mathematics is still low. This study aims to determine whether the application of the CTL (Contextual Teaching and Learning) learning model can increase interest in learning mathematics in VII students of SMP Muhammadiyah 8 Medan TP 2018/2019. This type of research is classroom action research (CAR) with the method used in this study. is qualitative. The subjects of this study were students of class VII-B SMP Muhammadiyah 8 Medan, totaling 34 students. The object in this study was the use of the CTL (Contextual Teaching and Learning) learning model to increase interest in learning mathematics for class VII-B students of SMP Muhammadiyah 8 Medan T.P 2018/2019 The data collection techniques in this study were observation, questionnaires and tests. Observations were used to obtain the results of observations of student interest in learning, the results of questionnaires of student interest in learning and tests were used to obtain the level of mastery of student learning and the implementation of the process of learning the subject matter of algebra using the Contextual Teaching and Learning model. The data analysis techniques used in this study were observational analysis, questionnaire analysis, learning completeness analysis and classical learning completeness analysis. The results showed an increase in students' interest in learning mathematics by using the Contextual Teaching and Learning model on the subject of algebraic forms in class VII-B students of SMP Muhammadiyah 8 Medan T.P 2018/2019. The improvements that occur are (1) in the early stages the average is 55 with a classical learning completeness percentage of 14.70%, (2) in the first cycle the observation average is 66.32 with a classical learning completeness percentage of 44.12%, (3) in the second cycle the average observation became 83.4 with the percentage of classical learning completeness 88.23%.